Systematic review : Natural Acne Patch Base On Nanomaterial Gelatin/Chitosan Bilayer from Mulberry Extract - Antan Saldaw; Lintang Tri Ananda; Muhammad Rafi Hafis; Shahibatul Wafa; Aden Dhana Rizkita (Proceeding International Conference on Religion, Science and Education, 2023)
This article discusses the development of an acne patch based on local mulberry ingredients which are extracted and then mixed into chitosan gelatin. The patch is made from the synthesis of galatin/chitosan nanomaterials with a mulberry extract capping agent. The characterization was carried out by looking at the morphology of the nanoparticles using SEM. The results obtained were that the particle shape was amorphous and was tested for anti-bacterial using the disc diffusion method on Staphylococcus aureus (S. aureus), Pseudonym aeruginosa (P. aeruginosa), and Escherichia coli (E. coli) bacteria. The results of the antibacterial test showed the ability of the galatin/chitosan nanoparticles of mulberry extract to have antibacterial activity by forming an inhibition zone with a diameter of 55 ± 2.25 mm. The patch was prepared by mixing a solution of gelatin and chitosan filled with mulberry extract, poured into a cup and dried at room temperature for 2 days. Then given 10% glutaraldehyde for 1 hour at 40oC. The results of the irritation test by applying the patch to the back for 4 hours showed no redness and swelling of the skin.